1997
DOI: 10.1055/s-2007-994190
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiopathological and Histopathological Effects of Fetal Distress on the Fetal Stomach: An Experimental Study

Abstract: Although effects of stress on the stomach have been extensively investigated in children and adults, our knowledge about effects of fetal distress (FD) on the fetal stomach is quite limited. Therefore, an experimental study was planned to evaluate the effects of FD on fetal gastric physiology and histology. In this study, a model of FD was created by way of intermittent maternal aortic occlusion in pregnant rabbits. In total, 21 fetuses of 6 pregnant rabbits were available for surgical and laboratory procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…14 Our previous study showed that gastric acid secretion was significantly increased and gastric damage occurred in the fetuses subjected to distress. 5 This observation led us to search for a preventive approach regarding the use of ranitidine. Although improving effects of the ranitidine on the stress-induced gastric damage is well known in children and adults, the present study showed that ranitidine failed in the prevention of fetal gastric damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Our previous study showed that gastric acid secretion was significantly increased and gastric damage occurred in the fetuses subjected to distress. 5 This observation led us to search for a preventive approach regarding the use of ranitidine. Although improving effects of the ranitidine on the stress-induced gastric damage is well known in children and adults, the present study showed that ranitidine failed in the prevention of fetal gastric damage.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous experimental study, we found that acute FD affects fetal stomach adversely through increased fetal gastric acid secretion and decreased fetal gastric PGE 2 , which results in gastric damage. 5 In this study, we condensed our efforts to prevent the harmful gastric effects that occur in the early period following FD. Accordingly, we aimed to determine whether prophylactic administration of ranitidine in acute FD prevents unfavorable physiopathological and histopathological effects seen in fetal stomach during early poststress period.…”
mentioning
confidence: 99%